If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 47 = 7x + 6(-1x + 6) Reorder the terms: 47 = 7x + 6(6 + -1x) 47 = 7x + (6 * 6 + -1x * 6) 47 = 7x + (36 + -6x) Reorder the terms: 47 = 36 + 7x + -6x Combine like terms: 7x + -6x = 1x 47 = 36 + 1x Solving 47 = 36 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 47 + -1x = 36 + 1x + -1x Combine like terms: 1x + -1x = 0 47 + -1x = 36 + 0 47 + -1x = 36 Add '-47' to each side of the equation. 47 + -47 + -1x = 36 + -47 Combine like terms: 47 + -47 = 0 0 + -1x = 36 + -47 -1x = 36 + -47 Combine like terms: 36 + -47 = -11 -1x = -11 Divide each side by '-1'. x = 11 Simplifying x = 11
| -48=4x+3(-4x+8) | | 74=3x+2(6x-8) | | 81=-2x-3(5x+7) | | x^2-36a^2+20x+100=0 | | -110=-2x+7(3x+6) | | 3(2x-1)-2=2(x+9)+1 | | x^2-16y^3=0 | | 23*3=23 | | 35+8x=7x+3 | | 2x(3x-4)+5=3x(2x-5)-4 | | 3a-2=2-2a+1 | | h=-16t^2+8t+80 | | H(t)=16t^2+144 | | -4x^2+22x+42=0 | | (2x-1)(2x-1)-25=0 | | (x-6)(x-6)-16=0 | | 3.5s=-38.5 | | k+2*k^2-15=0 | | r+4*r^2-5=0 | | -6x-2(-3x-1)(-3x-1)=0 | | (4x+3)(4x+3)-10=0 | | -5x^2-2x-2=0 | | 3.5*13= | | 3-(2x-4)=x+7 | | 7x-47=2 | | 3.5*13*1.5= | | (x)2+16x+64=0 | | (5x+2)(5x+2)-5=0 | | (4x+2)(4x+2)-36=0 | | 2x^2+x+4=0 | | 9x^2+6x-18=0 | | 9(u+4)=2u-34 |